2016
DOI: 10.1002/stem.2542
|View full text |Cite
|
Sign up to set email alerts
|

Proteome and Secretome Characterization of Glioblastoma-Derived Neural Stem Cells

Abstract: Glioblastoma multiforme (GBM) (grade IV astrocytoma) is the most common and aggressive primary brain tumor. GBM consists of heterogeneous cell types including a subset of stem cell-like cells thought to sustain tumor growth. These tumor-initiating glioblastoma multiforme-derived neural stem (GNS) cells as well as their genetically normal neural stem (NS) counterparts can be propagated in culture as relatively pure populations. Here, we perform quantitative proteomics to globally characterize and compare total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 62 publications
0
38
0
1
Order By: Relevance
“…However, in the in vivo tumor model described here, all tumor lipid bilayers are GFP-positive and thus it is not clear whether all GFP pos microglia have taken up EVs per se or may possibly have taken up tumor cell membrane debris. Other intercellular communication modes such as secreted molecules [69], exchange of molecules through gap junctions between cells [70], and cell connecting nano/microtubes may contribute to the observed effects as well. Glioma secreted cytokines (e.g., CSF-1, MCP-3, CX3CL1, SDF-1, and GM-CSF) that are especially known to be involved in the recruitment of microglial cells and could be responsible (in part) for the observed changes in gene expression, with EV-GFP uptake being a mere side-effect [3] Glioblastomas are heterogeneous tumors at the interand intratumor level and they express gene patterns associated with mesenchymal, proneural, and classical subtypes [71].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the in vivo tumor model described here, all tumor lipid bilayers are GFP-positive and thus it is not clear whether all GFP pos microglia have taken up EVs per se or may possibly have taken up tumor cell membrane debris. Other intercellular communication modes such as secreted molecules [69], exchange of molecules through gap junctions between cells [70], and cell connecting nano/microtubes may contribute to the observed effects as well. Glioma secreted cytokines (e.g., CSF-1, MCP-3, CX3CL1, SDF-1, and GM-CSF) that are especially known to be involved in the recruitment of microglial cells and could be responsible (in part) for the observed changes in gene expression, with EV-GFP uptake being a mere side-effect [3] Glioblastomas are heterogeneous tumors at the interand intratumor level and they express gene patterns associated with mesenchymal, proneural, and classical subtypes [71].…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, we observed a number of key GBM-associated genes that were not detected at the protein level and may reflect either a lack of translation or limitations of the MS-based approach used. MS-based proteomics has been used effectively by others to measure the proteome, secretome, and glycoproteins in immortalised GBM cell lines [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of spheroidal derivations in the growth dynamics in culture is believed to be the fundamental property of brain tumour stem cells (BTSC), which determines the initiation and proliferation of tumours in brain tissue (Laks et al, 2009) and is similar to the NSC/NPCs property to form the "neurospheres". It should be noted that the similarity of characteristics between the glioma cells and NSCs: a similar phenotype, proteome, secretome, comparable profile of receptor expression, adhesion molecules and identical targets of migration (Nakano, 2015;Yamamuro et al, 2015;Song et al, 2016;Amodeo et al, 2017;Garcia et al, 2017;Mehta & Lo Cascio, 2017;Qin et al, 2017) -is assumed as phylogenetic and it is suggested that brain tumours are derived from NSC/NPCs undergoing aberrant changes, -BTSCs (Kusne & Sanai, 2015;Stangeland et al, 2015;Zong et al, 2015;Ledur et al, 2016;Okawa et al, 2017). The content of BTSCs in glioma tissue enlarges proportionally with an increase in their malignancy, which is accompanied by raised expression levels of immunocytochemical markers of their stem phenotype (Bao et al, 2014;Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%